ANALISIS KEBUTUHAN MEDIA DAN TEKNOLOGI PEMBELAJARAN DI PONDOK PESANTREN DDI ABRAD MAKASSAR - Miftahul Khairah; Nurul Imam; Andi Ika Prasasti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the needs related to the use of learning media and technology at DDI Abrad Islamic Boarding School in Makassar. Employing a descriptive qualitative approach, data were collected through observation, semi-structured interviews, and questionnaires involving 12 tenth-grade students. The data analysis techniques included data reduction, data display, and conclusion drawing. The findings reveal that digital platforms such as Zoom, YouTube, and Google Forms have been utilized, although unevenly across subjects. The main challenges encountered include limited internet connectivity, lack of digital devices, and insufficient digital literacy. Meanwhile, the use of audiovisual media such as LCD projectors and PowerPoint presentations has been shown to enhance students’ learning motivation, active participation, and comprehension of the subject matter. Hence, there is a pressing need to improve digital infrastructure and increase digital competencies to support more interactive and effective learning experiences in the Islamic boarding school context.